2010
DOI: 10.1002/adfm.201001138
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Surface Chemistry and Electrocatalytic Properties of Monodisperse PtxNi1‐x Nanoparticles

Abstract: Monodisperse and homogeneous PtxNi1‐x alloy nanoparticles of various compositions are synthesized via an organic solution approach in order to reveal the correlation between surface chemistry and their electrocatalytic properties. Atomic‐level microscopic analysis of the compositional profile and modeling of nanoparticle structure are combined to follow the dependence of Ni dissolution on the initial alloy composition and formation of the Pt‐skeleton nanostructures. The developed approach and acquired knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
276
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(316 citation statements)
references
References 38 publications
31
276
3
4
Order By: Relevance
“…173 The intermediate composition with a Pt:Ni ratio of 1:1 exhibited the highest ORR activity (see Figure 4). 170 Matanovićet al 174 also selected three different Pt−Ni alloysPt 3 Ni 1 ,P t 1 Ni 1 , and Pt 1 Ni 3 to study the correlation between structure, reactivity, and stability using periodic DFT calculation.…”
Section: Impact Of Pt-alloy Composition On Orr Activitymentioning
confidence: 96%
“…173 The intermediate composition with a Pt:Ni ratio of 1:1 exhibited the highest ORR activity (see Figure 4). 170 Matanovićet al 174 also selected three different Pt−Ni alloysPt 3 Ni 1 ,P t 1 Ni 1 , and Pt 1 Ni 3 to study the correlation between structure, reactivity, and stability using periodic DFT calculation.…”
Section: Impact Of Pt-alloy Composition On Orr Activitymentioning
confidence: 96%
“…6,7 Therefore, to simultaneously decrease the use of Pt and enhance the intrinsic catalytic activity, transition metals (TMs) have been alloyed with Pt to produce bimetallic PtM (where M = Co, Fe or Ni) catalysts, which can be used as cathode materials for fuel cells. [8][9][10][11][12][13][14][15][16][17][18] The TMs are incorporated into the Pt lattice during nanoparticle synthesis, which causes compressive strain in the lattice and thereby decreases the Pt lattice constant. [9][10][11][12][13][14] It is also wellknown that electrons are transferred from the TMs to the Pt owing to the difference in their electronegativities.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high electronegativity difference (0.4) between them, some of the electrons in Co can transfer into the d-orbital of Pt, which could result in filling the Pt d-band and downshifting the d-band center energy. [9][10][11][12][13][14][15][16][17][18] As a result, the binding energy between the surface Pt and the O species (reaction intermediates such as -OOH and -OH) is weakened. These alloying effects of TMs have been described in many scientific reports using density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the ORR activity of our PtxNi1−x/C catalysts increased in the order of Pt1Ni1/C > Pt3Ni1/C > Pt1Ni3/C. Earlier studies have shown that electrochemical activated (after 25 potential cycles) PtxNi1−x catalysts have changed their bulk composition to roughly Pt3Ni and thus the residual bulk Ni will not be an sufficient descriptor for ORR activity [8,32]. In our present study, by using the EDX and ICP-AES analysis, we found that the atomic ratio of Pt/Ni after the initial potential cycling between 0.1 and 1.1 V versus the RHE for 50 cycles at 200 mV s −1 (in the section of electrochemical measurement) indeed changed to Pt3Ni1 regardless of their initial bulk composition.…”
Section: Resultsmentioning
confidence: 85%